Lessons from the COVID epicenter: how teacher candidates of color and the academy adapted to remote instruction. Issue 1 (4th January 2022) - Magaldi, Danielle; Fayne, Harriet
Abstract : Purpose: Given the challenges of remote learning and the pandemic's disproportionate impact on communities of color, this paper aims to present the voices of teacher candidates of color working on the frontlines of remote learning in communities of color hard-hit by the pandemic and to understand changes made in the shift to remote instruction for teacher education at the university level. Design/methodology/approach: Two teacher candidate narratives are presented as case studies along with findings from a self-study on the changes necessitated by remote instruction in two teacher preparation courses at the university level. Findings: Findings underscore teacher candidates' fortitude amidst compound stress. Emergent themes included flexibility, adapting, reaching out for help, problem-solving and drawing on their own experiences. Themes also included struggle, fatigue and feelings of incompetence. At the university level, teacher education preparation required flexibility and opening up space for collaborative problem-solving. Originality: In urban communities of color, pre-pandemic disparities in under-resourced public schools not only persisted but were intensified by the pandemic's unequal impact on people of color. This study foregrounds the voices and experiences of teacher candidates of color teaching remotely, providing contributions to the field derived from their lived experiences. Their voices are essential data, bringing much needed attention to obstacles of remote teaching in communities of color and to the resourcefulness teacher candidates demonstrated in service of multicultural education.